Absence of Excretion of the Active Moiety of Bisacodyl and Sodium Picosulfate into Human Breast Milk: an Open-label Parallel-group, Multiple-dose Study in Healthy Lactating Women - Friedrich, Christian; Richter, Erika; Trommeshauser, Dirk; De Kruif, Sandra; van Iersel, Thijs; Mandel, Ken; Gessner, Ulrika (Drug metabolism and pharmacokinetics, 2011)
The aim of this study was to determine whether administration of the prodrugs bisacodyl (Bisa) and sodium picosulfate (SPS) leads to excretion of their common active metabolite, bis-(p-hydroxyphenyl)-pyridyl-2-methane (BHPM), in breast milk. Two groups of 8 healthy lactating women who had stopped breast feeding received multiple doses of Bisa or SPS. Plasma, urine, and breast milk were collected and concentrations of free and total BHPM were determined using validated liquid chromatography/mass spectrometry methods. BHPM remained below the limits of detection in breast milk following single- and multiple-dose administration of Bisa and SPS. First, BHPM plasma concentrations were observed after a lag time of about 3 to 4 h and 4 to 5 h following Bisa and SPS administration, respectively. Cmax was attained approximately 5 h after dosing of Bisa and 9 h after dosing of SPS. BHPM did not accumulate after multiple administrations of Bisa and only slightly accumulated following multiple doses of SPS. About 12% and 13% of Bisa and SPS was excreted as BHPM into urine at steady state. BHPM, the active moiety of Bisa and SPS, was not excreted into human breast milk. Hence, use of Bisa or SPS to treat constipation of breast-feeding women is considered well tolerated with regard to exposing infants to BHPM via breast milk.